Perspectives and Experiences of Parents and Adolescents Who Participate in a Pediatric Precision Oncology Program: "When You Feel Helpless, This Kind of Thing Is Very Helpful". (31st March 2022) - Waldman, Larissa; Hancock, Kelly; Gallinger, Bailey; Johnstone, Brittney; Brunga, Ledia; Malkin, David; Barrera, Maru; Villani, Anita
Abstract : PURPOSE: The SickKids Cancer Sequencing (KiCS) Program, launched in 2016, evaluates the clinical utility of paired tumor/germline Next-Generation Sequencing (NGS) in pediatric oncology patients with hard-to-cure and rare cancers. In anticipation of further widespread adoption of NGS, we aimed to characterize the experiences and perspectives of adolescents and parents of patients who have already undergone NGS evaluation, focusing on the psychosocial impact and personal utility. METHODS: Parents of patients with pediatric cancer and adolescent patients who have participated in KiCS were invited to participate in semistructured interviews. Transcripts were analyzed using an inductive content analytic approach. RESULTS: Of 45 individuals invited, 22 parents and 10 adolescents were interviewed (71% response rate). Prominent psychosocial themes were low distress, relief, and sense of control; some expressed fear of the unknown. In exploring constructs of personal utility, parents highlighted hope for treatment options despite low expectations for results with clinical impact, whereas adolescents articulated altruistic motivations and less hope for personal clinical benefit. Bringing closure and answering the question of why the cancer occurred was a salient theme among both groups. Both parents and adolescents find benefit and clear decisional satisfaction with participation. No participants expressed regret. CONCLUSION: This study suggests that parents and adolescents benefit from NGS evaluation beyond the return of clinically relevant results. Our findings lay the framework for future work evaluating the value of NGS in pediatric precision oncology care through assessment of patient-reported outcomes and experiences. These results also guide provision of pre- and post-test education and support, which will facilitate patient-centered delivery of NGS practices.